STELARR Volume I—Global opportunities for rangelands restoration through livestock value chains - Baker, Derek (International Livestock Research Institute, 2025)
This report is part of the project Sustainable Investments for Large-Scale Rangelands Restoration (STELARR), whose general objective is to reverse the degradation of rangelands globally through sustainable livestock value chains, reduce poverty and ensure livelihoods with inclusive benefits for women and youth. It is accompanied by three regional studies undertaken in Latin America, Africa, and Middle East and Central Asia. This study examines ‘sustainable luxury’ as a source of investment in rangelands’ restoration. It recognizes rangelands users cannot pay for rangeland restoration and identifies the retail margins charged by luxury brand owners as a source of investment. Investment models that deliver win-win solutions to both the owners of luxury brands and rangelands users are identified and discussed for a selection of rangeland value chains. These models depart from conventional development finance project designs which target smallholder and community benefits and address the renewal of rangelands for the benefit of all stakeholders in value chains. Emphasis is given to developments in information availability for rangelands and in value chains. This encompasses the STELARR project’s components, private sector developments, and multistakeholder action in establishing standards that invite value addition by rangeland users.